Pengembangan Karakter Empati Siswa Madrasah Ibtidaiyah Melalui (Strategi Pembelajaran) - Barotuttaqiyah Barotuttaqiyah; Siti Mumun Muniroh (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
The development of empathy character in Madrasah Ibtidaiyah students plays a crucial role in shaping a generation that is not only intellectually intelligent but also socially sensitive. This study aims to explore effective learning strategies to instill empathy in students. The method employed is a literature review by analyzing various sources related to Islamic value-based learning strategies. The findings indicate that strategies such as project-based learning, simulations, reflective discussions, story-based learning, collaborative activities, and social actions effectively foster empathy. These strategies provide profound emotional and social experiences while aligning with Islamic teachings. For example, storytelling about prophets and charity activities effectively instill empathy through direct and contextual experiences. In conclusion, fostering empathy requires a holistic approach integrating practical experiences with Islamic values. Educators are advised to receive training on implementing these strategies, while parents should model empathetic behavior at home. Future research is recommended to empirically evaluate the effectiveness of these strategies in various educational settings.